(untitled) (Bangladesh Journal of Medicine, 2021)
Background: The severe acute respiratory syndrome (SARS) causing the COVID 19 pandemic infection has affected one and all across the world and halting mosthuman activities. During the disease outbreak and country lockdown, Blood Transfusion Services faced numerous challenges to maintain the sustainability in service provision. We intend to identify the challenges faced during COVID-19 outbreak and the following imposed national lockdown. Methods: This retrospective study was done during the lockdown period from26/03/2020 to 30/05/2020 comprising 66 days to detect donor inflow declination and to compare the donor inflow with pre lockdown and post lockdown period of same duration. The periods were divided into six equal intervals to compare donor distribution patterns in lockdown, pre lockdown and post lockdown period. Mean and standard deviation was calculated for continuous variables and chi square test was done for categorical variables. Results: The donations collected during the lockdown period and post lockdown period were almost 71.37% and 62.82% less respectively when compared with the pre lockdown collection (211and 274 versus 737).While in interval periods, donor inflow was declined substantially in lockdown period and in post lockdown period, inflow was declined as of lockdown period initially but it increases as time passed. But the increment was not as such of pre lockdown period. Donor inflow in age group and time interval of donation frequency were statistically significant (p <0.00005 and p< 0.0037 respectively). Conclusion: Concerns of being infected through hospital contact, lack of public transport facilities, travel restrictions imposed by the police department, and no availability of medical student donors in the hospital setting were the main attributing factors for donor inflow. Bangladesh J Medicine July 2022; 33(1) : 70-75